(untitled) (Vietnam Journal of Community Medicine, 2022)
Introduction: Priapism is a rare condition, in which high-flow priapism is the least common (<5%). Methods: A high-flow priapism was diagnosed and treated by selective arterial embolisation at People’s Hospital 115. Results: A 57-year-old male was hospitalised with penile erection lasting 10 days. The patient was examined and diagnosed with bilateral cavernosal arteries laceration. After applying conservative management such as cold compress, perineal compression, the penile erection still does not improve. The patient underwent selective arterial embolisation of laceration cavernosal branches. Then the penile return to the normal detumescence state. Discussions: Selective arterial embolisation is quite effective in this condition, the success rate in some studies ranges between 61,7 and 83,3%, and erectile dysfunction (ED) rate ranges from 8-33%. Conclusion: Selective arterial embolisation in high-flow priapism is a minimally invasive, safe, and effective method. However, the ED rate is still high.